2016
DOI: 10.1111/cen.13135
|View full text |Cite
|
Sign up to set email alerts
|

Increased peroxiredoxin 4 levels in patients with prediabetes compared to normal glucose tolerance subjects

Abstract: The levels of peroxiredoxin 4 are higher in patients with prediabetes, but are similar in subjects with and without insulin resistance, which suggests that the main factor for its increased levels is hyperglycaemia and not insulin sensitivity state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
3
2
0
Order By: Relevance
“…Therefore, clinically, specific accelerators of PRDX4 may prove useful as therapeutic agents for protecting against the initiation and progression of DM, atherosclerosis, NAFLD, and subsequently metabolic syndrome in humans by suppressing oxidative damage and pro‐apoptotic or inflammatory factors throughout the course of these diseases. By contrast, one paper more recently published has reported that the plasma PRDX4 levels are significantly higher in patients with prediabetes . In line with that, we have also found that patients with type 2 DM show significantly higher serum hPRDX4 levels than healthy adult volunteers, potentially due to the greater demand for antioxidant defense in type 2 DM.…”
Section: Intriguing Topics For Future Studies and Concluding Remarks supporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, clinically, specific accelerators of PRDX4 may prove useful as therapeutic agents for protecting against the initiation and progression of DM, atherosclerosis, NAFLD, and subsequently metabolic syndrome in humans by suppressing oxidative damage and pro‐apoptotic or inflammatory factors throughout the course of these diseases. By contrast, one paper more recently published has reported that the plasma PRDX4 levels are significantly higher in patients with prediabetes . In line with that, we have also found that patients with type 2 DM show significantly higher serum hPRDX4 levels than healthy adult volunteers, potentially due to the greater demand for antioxidant defense in type 2 DM.…”
Section: Intriguing Topics For Future Studies and Concluding Remarks supporting
confidence: 89%
“…By contrast, one paper more recently published has reported that the plasma PRDX4 levels are significantly higher in patients with prediabetes. 60 In line with that, we have also found that patients with type 2 DM show significantly higher serum hPRDX4 levels than healthy adult volunteers, 8 potentially due to the greater demand for antioxidant defense in type 2 DM. Nevertheless, PRDX4 would have pathophysiological relevance for protecting against metabolic syndrome in humans.…”
Section: Intriguing Topics For Future Studies and Concluding Remarks supporting
confidence: 77%
“…According to the previous reports, other PRX members including PRX1, PRX2, PRX4, and PRX6 respond actively to glucose and/or insulin-related oxidative stress [28–30]. In the present study using mouse islet cells, the oxidation of PRX3 was quite fewer as compared to that of PRX1 and/or PRX2 under basal conditions.…”
Section: Discussionsupporting
confidence: 45%
“…In contrast, our results showed an association between Prx4 and insulin resistance in PCOS women although we found no association with glucose levels. Differences in the disease type and the number of samples may be the cause of difference in results [ 42 ].…”
Section: Discussionmentioning
confidence: 99%